Annual report of the Department of Agriculture (animal husbandry research), 1968/1969 - University of Malawi (1972)
Summarizes trial results and observations on growth, conception rates and slaughter statistics of Malawi Zebu (MZ) cattle and sheep. Research finding on milk yield of MZ cows, performance testing of MZ and crossbred calves, stall feeding and grazing, beef production with MZ steers and production of other livestock at different research sites in Malawi are reported.